2018
DOI: 10.14745/ccdr.v44i11a06
|View full text |Cite
|
Sign up to set email alerts
|

CPHLN recommendations for the laboratory detection of Shiga toxin-producing Escherichia coli (O157 and non‑O157)

Abstract: Shiga toxin-producing Escherichia coli (STEC) are important enteric pathogens responsible for sporadic cases and outbreaks of gastroenteritis. E.coli O157:H7/NM (STEC O157) are the most commonly known STEC serotypes but it is now increasingly apparent that non-O157 STEC serotypes have been underreported in the past because they were not part of routine screening in many front-line laboratories. The Canadian Public Health Laboratory Network (CPHLN) has identified the need for improved detection and surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…do not yet routinely test for them (10). Nonetheless, by 2016, approximately 35% of all STEC infections reported to the Canadian National Enteric Surveillance Program were caused by non-O157 serotypes (11).…”
Section: Introductionmentioning
confidence: 99%
“…do not yet routinely test for them (10). Nonetheless, by 2016, approximately 35% of all STEC infections reported to the Canadian National Enteric Surveillance Program were caused by non-O157 serotypes (11).…”
Section: Introductionmentioning
confidence: 99%
“…According to the EU One Health Zoonosis report in 2020, there was an overall trend for reporting STEC cases between 2015 to 2019 due to the awareness of the importance of STEC detection associated with outbreaks in the EU [21]. In Canada, there was a recommendation in 2018 from the Canadian Public Health Laboratories Network for all Canadian laboratories to detect all STEC, especially the non-O157, for better surveillance purposes [14]. An outbreak of O121 in 2016 linked to wheat flour was confirmed using pulsed-field gel electrophoresis and whole genome sequencing [22], of which both techniques require growth of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that non-O157 STEC isolates can be difficult to enrich in certain broth media, suggesting a potential for mixed infections that can be missed during an outbreak [13]. Culture-independent diagnostic tests (CIDT), which detect the presence of the stx gene(s), are becoming more readily available, allowing for rapid diagnosis, as well as increased surveillance [14,15]. CIDT are optimal for diagnostic identification, as they do not require culture prior to testing, which greatly decreases the turnaround time.…”
Section: Introductionmentioning
confidence: 99%
“…Classical STEC detection algorithms were primarily targeted at biochemical differences specific to O157 STEC and missed a significant proportion of non-O157 STEC [4]. Newer detection algorithms have been implemented with the aim to improve the detection of non-O157 serogroups [5]. The 2017 Infectious Diseases Society of America (IDSA) guidelines recommended that STEC screening should include an enzyme immunoassay (EIA) or nucleic acid amplification test (NAAT) for the detection of non-O157 along with O157 strains [6].…”
Section: Introductionmentioning
confidence: 99%